Effective Model MTS Nahdlatul Ulama Medan and Mts Taman Pendidikan Islam Medan To Implement Inclusive Education - Surianto, Surianto; Ananda, Rusydi; Nurmawati, Nurmawati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe the concept of inclusive education by looking at the obstacles faced, and the efforts made to overcome these obstacles in realizing the implementation of inclusive education at MTs Taman Pendidikan Islam and MTs Nadhlatul Ulama. This research method is a qualitative research method with a multi-site design. Data collection techniques used are observation, interviews, and documentation studies. The informants in this study numbered ten people, with a distribution of five people from MTs Nadhlatul Ulama Medan and five people from MTs Taman Pendidikan Islam. Data processing consists of data reduction, data presentation, data analysis, and drawing conclusions. The results of the study show that the concept of inclusive education in Medan city madrasas emphasizes education that provides an equal learning environment for all students regardless of existing differences through the principle of diversity. The implementation of inclusive education is also encouraged through provision of teachers through inclusive education training by inviting inclusive education experts/consultants and the training materials presented are in the form of an understanding of the needs of students with special needs, effective learning, to the use of appropriate learning aids. Inclusive education is also encouraged through the optimization of a more flexible curriculum by modifying it according to student needs. Meanwhile, efforts made to overcome obstacles in implementing inclusive education include seeking assistance from external institutions, participating in online inclusive education training, developing a more flexible curriculum, involving related communities in every activity, and establishing regular communication with parents.